The mode of choice for non-mandotary activities, case studies in Kota Bharu, Kelantan - Siti Rohani , Mohamad (2015)
In other to understand the reason how and why citizen of Kota Bharu Kelantan choose to travel by public transport or private vehicles, a study was conducted to investigate the mode of choices for non-mandatory activities. The objectives of this studies is to understand the influence of family household profiles and numbers, with the mode choice of transportation and to study the influence of vehicle ownership as well as to study the most influencing factors behind mode choices for choosing the transportation, such as distance time saving, cost saving, comfort choices, captive or no other choices, and other reason. Data was collected using questionnaire to relate the most influencing factors for choosing mode of transportation with different situation when travelling such as alone, coupled, more than two people, during night time, and day time. The reason includes for each mode choices based on situation and distance base are time saving, cost saving, comfort choices, captive/ no other choices and others. From the data of short distance travelled the pattern of mode choices for these studies are car and motorcycle as the most influence factor known from the data collected when travelling short distance are time and cost saving. As for medium distance travelling they tend to used car and the highest reason are time saving and comfort choices. Meanwhile for long distance travelled respondent tend to use bus and car because of time saving and comfort choices. From the result mode choices of choosing transport for nonmandatories activities are understandable and research objective are achieves.